Inhibitory Effect of Damulin B from Gynostemma pentaphyllum on Human Lung Cancer Cells - Xing, Shao-Fang; Liu, Lin-Hua; Zu, Ma-Li; Lin, Man; Zhai, Xin-Fang; Piao, Xiang-Lan (Planta Medica, 2019)
Damulin B, a dammarane-type saponin from steamed Gynostemma pentaphyllum, exhibits the strongest activity against human lung carcinoma A549 cells among the isolated active saponins. In this study, the structure-activity relationship of a series of saponin compounds was discussed. The inhibitory effect of damulin B on human lung cancer A549 and H1299 cells was investigated from apoptosis, cell cycle, and migration aspects. In vitro, human lung cancer cells were more susceptible to damulin B treatment than human normal fibroblasts. Damulin B exhibited a strong cytotoxic effect, as evidenced by the increase of apoptosis rate, reduction of mitochondrial membrane potential (MMP), generation of reactive oxygen species, and G0/G1 phase arrest. Furthermore, damulin B activated the following: both intrinsic and extrinsic apoptosis pathways along with early G1 phase arrest via the upregulation of the Bax, Bid, tBid, cleaved caspase-8, and p53 expression levels; downregulation of the procaspase-8/-9, CDK4, CDK6, and cyclin D1 expression levels; and more release of cytochrome c in the cytoplasm. In addition, antimigratory activities and suppressive effects on metastasis-related factors, such as MMP-2 and MMP-9, accompanied by the upregulation of IL-24 were revealed. Altogether, the results proved that damulin B could inhibit human lung cancer cells by inducing apoptosis, blocking the cell cycle at early G0/G1 phase and suppressing the migration. Hence, damulin B has potential therapeutic efficacy against lung cancer.
Keywords: Gynostemma pentaphyllum; Curcubitaceae; saponin; damulin B; cytotoxicity; lung cancer